Beware the British serpent : the role of writers in British propaganda in the United States, 1939-1945 - Calder, Robert, 1941- (McGill-Queen's University Press, 2004)
During World War II, the United States was the target of what Gore Vidal has called "the largest, most intricate and finally most successful conspiracy directed at it in the twentieth century"--Great Britain's "vast conspiracy to manoeuvre an essentially isolationist country into the war." In Beware the British Serpent Robert Calder examines British writers' involvement in this propaganda campaign, including lecturing and touring in the United States, broadcasting on American radio, writing screenplays for films such as Mrs. Miniver and This Above All, and writing articles and books for publication in America